N88S seipin-related seipinopathy is a lipidopathy associated with loss of iron homeostasis - Mariana O. Ribeiro; Mafalda Oliveira; Verónica Nogueira; Vítor Costa; Vitor Teixeira (Cell Communication and Signaling)
Abstract Background Seipin is a protein encoded by the BSCL2 gene in humans and SEI1 gene in yeast, forming an Endoplasmic Reticulum (ER)-bound homo-oligomer. This oligomer is crucial in targeting ER-lipid droplet (LD) contact sites, facilitating the delivery of triacylglycerol (TG) to nascent LDs. Mutations in BSCL2, particularly N88S and S90L, lead to seipinopathies, which correspond to a cohort of motor neuron diseases (MNDs) characterized by the accumulation of misfolded N88S seipin into inclusion bodies (IBs) and cellular dysfunctions. Methods Quantitative untargeted mass spectrometric proteomic and lipidomic analyses were conducted to examine changes in protein and lipid abundance in wild-type (WT) versus N88S seipin-expressing mutant cells. Differentially expressed proteins were categorized into functional networks to highlight altered protein functions and signaling pathways. Statistical comparisons were made using unpaired Student's t-tests or two-way ANOVA followed by Tukey´s / Šídák's multiple comparisons tests. P-values < 0.05 are considered significant. Results In a well-established yeast model of N88S seipinopathy, misfolded N88S seipin forms IBs and exhibits higher levels of ER stress, leading to decreased cell viability due to increased reactive oxygen species (ROS), oxidative damage, lipid peroxidation, and reduced antioxidant activity. Proteomic and lipidomic analyses revealed alterations in phosphatidic acid (PA) levels, associated with disrupted inositol metabolism and decreased flux towards phospholipid biosynthesis. Importantly, deregulation of lipid metabolism contributed to ER stress beyond N88S seipin misfolding and IB formation. Additionally, the model exhibited deregulated iron (Fe) homeostasis during lifespan. N88S seipin-expressing cells showed impaired ability to cope with iron deficiency. This was linked to changes in the expression of Aft1p-controlled iron regulon genes, including the mRNA-binding protein CTH2 and the high-affinity iron transport system member FET3, in a p38/Hog1p- and Msn2p/Msn4p-dependent manner. Importantly, we unraveled a novel link between inositol metabolism and activation of the iron regulon in cells expressing the N88S seipin mutation. Despite iron accumulation, this was not associated with oxidative stress. Conclusions The study highlights that the effects of N88S seipin mutation extend beyond protein misfolding, with significant disruptions in lipid metabolism and iron homeostasis. This research marks a substantial advance in understanding and defining the roles of proteins and signaling pathways that contribute to human seipinopathy. Altered cellular processes, as well as potential therapeutic targets and biomarkers, were identified and can be explored in translational studies using human cell models.